Transformation of foreign commerce of Ukraine: realities, problems, perspectives - Гусєва, Наталія; Кандиба, Юрій; Кобилін, Павло (Human Geography Journal, 2019)
The paper analyzes transformations of foreign trade in goods of Ukraine in 2000-2017. The choice of the study period is due to the fact that the "recovery" and the gradual growth of the Ukrainian economy after the long crisis of the 1990s has began since 2000. Ukraine had a mostly negative foreign commercial balance (except for 2000-2004 and 2015); generally balanced foreign trade; dangerous import dependency ratio; extremely economy openness index; the high exports ratio in 2000-2017. The volumes of export, imports and foreign commercial turnover had unstable dynamics with negative trends in 2008-2009 and 2013-2015. Base metals and their ware; plant products; animal or plant fats and oils were prevailed in the export component of the foreign commerce; mineral products; machines, equipment and mechanisms, electric and technical equipment; products of chemical and derivative industries were dominant in the structure of import in 2017. The export was characterized by increase in the share of products of the primary sector (due to crop production) and decrease in the secondary sector (due to metallurgy, machine building, chemical and textile industry) during 2001-2017. The import was characterized by decrease in the share of raw materials and increase in the share of all other goods during the mentioned period. Commodity structure of foreign trade became more proportional, without a highly dominant product. The Russian Federation, Poland, Turkey, Italy, India were the key partners in the export of goods, while those ones in the import were the Russian Federation, China, Germany, Poland, Belarus. The key partners remained during 2001-2017 (the Russian Federation, Poland, Turkey, Italy, China, Germany were key partner in export; In the import - the Russian Federation, Germany, Poland, Belarus, the USA, Italy were key partner in import. Despite the drastic decrease in trade relations with the Russian Federation, it remains the largest partner in the Ukrainian foreign commerce. Among the regions of the world, the largest trading partner of Ukraine in recent years is Europe with relevant reduction of CIS countries in the common share. It is necessary to provide a set of measures aimed at increasing the efficiency of export activity and import substitution in the certain sectors of the economy to balance foreign commerce of Ukraine.